Harmoni dalam Perbedaan: Komunikasi Antarbudaya pada Masyarakat Transmigran di Kampung Bali Kabupaten Musi Rawas - Rama Wijaya Kesuma Wardani (Faculty of Dakwah and Communication, UIN Syarif Hidayatullah Jakarta, 2020)
AbstractThe people of South Sumatra are very diverse in terms of culture, language, and religion. This article is aimed to explore the portrait of religious harmony between Hindus who are mostly Balinese and Muslims who are actually indigenous people (of Musi Rawas) and Javanese in Kampung Bali, Musi Rawas, South Sumatra. The method of this research is qualitative, and this type of research is phenomenology. One of the research findings is a variety of factors that support the realization of harmony among religious people in Kampung Bali: first, cultural factors; second, social interaction and dialogue between religious leaders of Hinduism and Islam; third, figures who engage in the social environment; fourth, the bond of a religious collaboration to meet the needs of life. AbstrakMasyarakat Sumatera Selatan sangat beragam dalam hal budaya, bahasa, dan agama. Tulisan ini bertujuan untuk mengeksplorasi potret kerukunan umat beragama antara umat Hindu yang sebagian besar orang Bali dan Muslim yang merupakan masyarakat asli (Musi Rawas) dan Jawa di Kampung Bali, Musi Rawas, Sumatera Selatan. Metode penelitian ini adalah kualitatif, dan jenis penelitiannya adalah fenomenologi. Salah satu temuan penelitiannya adalah berbagai faktor yang mendukung terwujudnya kerukunan umat beragama di Kampung Bali: pertama, faktor budaya; kedua, interaksi sosial dan dialog antara pemuka agama Hindu dan Islam; ketiga, tokoh yang terlibat dalam lingkungan sosial; keempat, ikatan kolaborasi agama untuk memenuhi kebutuhan hidup.